Effects of different set configurations on barbell velocity and displacement during a clean pull - Haff, G. G.; Whitley, A.; McCoy, L. B.; O'Bryant, H. S.; Kilgore, J. L.; Haff, E. E.; Pierce, K.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2003)
The effects of 3 types of set configurations (cluster, traditional, and undulating) on barbell kinematics were investigated in the present study. Thirteen men (track and field = 8; Olympic weightlifters = 5) (mean ± SEM age, 23.4 ± 1.1 years; height, 181.3 ± 2.1 cm; body mass, 89.8 ± 4.2 kg) performed 1 set of 5 repetitions in a cluster, traditional, and undulating fashion at 90 and 120% of their 1 repetition maximum (1RM) power clean (119.0 ± 4.3 kg). All data were collected at 50 Hz and analyzed with a V-Scope Weightlifting Analysis System. Peak velocity (PV) and peak displacement (PD) were analyzed for each repetition and averaged for each set type. Results indicated that a significantly (p < 0.016) higher PV occurred during the cluster set when compared with the traditional sets at both intensities. PD was significantly higher than traditional sets at the 120% intensity. The present study suggests set configuration can affect PV and PD during clean pulls.